Student Entrepreneurship Training Through the Campus Business Incubator at the Faculty of Entrepreneurship, Universitas Garut - Sugiarto, Hendro; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam; Dahlena, Alni; Isani, Aura (Indonesian Journal of Community Empowerment (IJCE), 2025)
The problem is that students' understanding of the importance of entrepreneurial competencies in today's workplace is unequal. Many students still view entrepreneurship as a last resort, rather than a primary career path. The method employed emphasizes the integration of theory-based entrepreneurship training with hands-on practice through the utilization of the Campus Business Incubator. The results of this training activity indicate that, through the active use of the Campus Business Incubator, students gain not only knowledge but also real-world experience and mentoring relevant to current market needs. The success of this activity provides an important foundation for the Faculty of Entrepreneurship at Garut University to continue and develop similar programs on an ongoing basis. Incubation-based entrepreneurship training is highly effective in preparing students to become innovative and independent young entrepreneurs.